Institutional reform in the Burkinabè cotton sector and its impacts on incomes and food security: 1996-2006 - Kaminski, Jonathan; Headey, Derek D.; Bernard, Tanguy (International Food Policy Research Institute, 2009)
Like other West African cotton producers, Burkina Faso’s cotton strategy has traditionally involved substantial government intervention in both input and output markets. Despite some notable successes, this state-led strategy became widely criticized by the late 1980s for inefficiencies, inequities, and for inducing macro-economic instability. However, Burkina Faso rejected both the status quo and wholesale liberalization paths, and instead embarked on a more gradual and sequenced reform path that included strengthening farmers’ groups before partially liberalizing input and output markets. Although these reforms have coincided with Burkina Faso becoming the largest cotton exporter in Africa, this paper more rigorously assesses the success of these reforms through both descriptive evidence and a counterfactual analysis of what might have happened if the prereform status quo had continued. We conclude that the reforms were highly successful in terms of production growth, job creation, and in improving nutrition and poverty reduction among cotton producers. However, we also consider important caveats. Partly by design, the reforms were less successful at raising yields, stimulating development in the broader economy, and addressing environmental concerns. The more damaging criticism that the reforms have proved financially unsustainable is also considered. Without being apologist, we argue that the new institutions created under the cotton reforms at least provide a deliberative forum for successfully addressing the problem. A key challenge for the near future will be to ensure that the key institutions in this forum–particularly the farmers union and the former parastatal–are made more accountable to farmers and other key actors in the cotton sectors.